Analisis Daya Dukung Wilayah (Carrying Capacity Ratio) Sebagai Salah Satu Alat Analisis Dalam Perencanaan Pertanian Daerah (Studi Tentang Daya Dukung Wilayah Pertanian Tanaman Pangan di Kabupaten Belu) - Manek, Januarius Meinaldo (Jurnal Administrasi Publik, 2015)
Abstract: Analysis of Regional Support (Carrying Capacity Ratio) As One Analysis Tools In the Regional Agricultural Development Planning (Studies on the Carrying Capacity of Regional Agriculture in Belu Regency East Nusa Tenggara Province). CCR analysis is one tool in the analysis of agricultural development planning area that can describe the state of the carrying capacity of the area agricultural region. CCR analysis has never been used in Belu that this analysis needs to be done in order to give a picture of the carrying capacity of agricultural areas for the preparation of the Belu district agricultural planning in the future .. The results of this study indicate that the carrying capacity of agricultural land in Belu for: rice crop (rice) and soybeans in Belu district has not been able to meet the needs of the population and does not have a soybean crop farms. As for the bearing capacity of agricultural land plant sweet potatoes, peanuts, corn, cassava, and green beans are still very able to meet the needs of the population Belu district. Keywords: Carrying Capacity, Regional Agricultural Development Planning, Plant Food. Abstract: Analisis Daya Dukung Wilayah (Carrying Capacity Ratio) Sebagai Salah Satu Alat Analisis Dalam Perencanaan Pembangunan Pertanian Daerah (Studi Tentang Daya Dukung Wilayah Pertanian Tanaman Pangan Di Kabupaten Belu Provinsi  Nusa Tenggara Timur). Analisis CCR merupakan salah satu alat analisis dalam perencanaan pembangunan pertanian daerah yang dapat menggambarkan  keadaan daya dukung wilayah pertanian daerah. Analisis CCR belum pernah digunakan di Kabupaten Belu sehingga analisis ini perlu dilakukan agar dapat memberikan gambaran keadaan daya dukung wilayah pertanian bagi penyusunan perencanaan pertanian Kabupaten Belu ke depannya.. Hasil dari penelitian ini menunjukan bahwa kemampuan daya dukung lahan pertanian di Kabupaten Belu untuk tanaman padi (sawah) dan kedelai yang ada di Kabupaten Belu belum mampu untuk memenuhi kebutuhan penduduk dan tidak memiliki lahan pertanian tanaman kedelai. Sedangkan  untuk kemampuan daya dukung lahan pertanian tanaman ubi jalar, kacang tanah, jagung, ubi kayu,  dan kacang hijau masih sangat mampu untuk memenuhi kebutuhan penduduk Kabupaten Belu.